1962
DOI: 10.1172/jci104650
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Urinary Hydroxyproline and Growth*

Abstract: Beginning with the report of Ziff, Kibrick, Dresner, and Gribetz (2), evidence accumulated in recent years has indicated that urinary hydroxyproline excretion reflects collagen metabolism, since collagen is the only protein in the body that contains hydroxyproline in significant amounts (3). Ziff and co-workers, observing that the excretion of this amino acid in peptide form was greater in children than in adults, suggested that the level of urinary hydroxyproline might be related to the size of the metabolica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
1
6

Year Published

1963
1963
1981
1981

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(55 citation statements)
references
References 17 publications
0
48
1
6
Order By: Relevance
“…Disorders in which rates of urinary excretion of hydroxyproline are depressed include malnutrition, hypothyroidism and dwarfism, whether of pituitary or other nature, and infantile protein-calorie malnutrition [6,7,11,13,17,181. Disorders associated with increased rates of urinary excretion of hydroxyproline include hyperthyroidism, malabsorption syndromes, rickets and vitamin D-resistant rickets.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Disorders in which rates of urinary excretion of hydroxyproline are depressed include malnutrition, hypothyroidism and dwarfism, whether of pituitary or other nature, and infantile protein-calorie malnutrition [6,7,11,13,17,181. Disorders associated with increased rates of urinary excretion of hydroxyproline include hyperthyroidism, malabsorption syndromes, rickets and vitamin D-resistant rickets.…”
Section: Commentmentioning
confidence: 99%
“…A numtively great. In view of this considerable contribution ber of studies have suggested that rate of urinary excreof newly formed collagen to urinary excretion of hydrotion of hydroxyproline reflects rate of collagen metaxyproline, it is not surprising that rates of excretion, exbolism [2,6,7,8,9,11,13,15,17,18, 191. Studies of pressed as milligrams/day, have generally been reporthydroxyproline excretion may therefore be clinically ed to be somewhat greater in children than in adults.…”
mentioning
confidence: 99%
“…proline during infancy, childhood and adolescence has been defined and it has been shown that during periods The rate of urinary excretion of endogenous hydroxy-of rapid linear growth, the amount of total hydroxyproiine, both free and in peptide form, is related to the proline excreted increases [8,9,26]. There is little inmetabolic state and total mass of body collagen [2, 13, formation, however, about hydroxyproiine excretion 21].…”
Section: Introductionmentioning
confidence: 99%
“…The excretion o f total hydroxyproline (THP) is greater in normal children than in adults (Prockop & Kivirikko 1967) and it increases with increasing growth rate (Jasin et al 1962, Jones et al 1964, Smiley & Ziff 1964. The higher concentration of THP found in the urine of IS patients could be caused by an accelerated growth (Zorab et al 1971).…”
mentioning
confidence: 99%